Prognostic Value of C4d Immunolabelling in Adult Patients With IgA Vasculitis - Romero, Anais; Drieux, Fanny; François, Arnaud; Dervaux, Alexandra; Xu, Xiao Li; Titeca-Beauport, Dimitri; Bertrand, Dominique; Guerrot, Dominique (Frontiers in Medicine, 2021)
Background and objectives: Glomerular C4d deposits are associated the severity and outcomes of IgA nephropathy. Whether this holds true in immunoglobulin A vasculitis (IgAV) is not known. The main objective of the study was to analyze the prognostic value of glomerular C4d immunolabelling on kidney impairment in adults with IgAV. Design, setting, participants, measurements: This retrospective cohort study included 120 adults with IgAV and a kidney biopsy performed between 1995 and 2018 in two French university hospital centers. All paraffin-embedded biopsies were reassessed according to Oxford classification. Immunofluorescence for C4d was performed in all cases. For analysis, patients were grouped according to positivity for C4d in the mesangial area. The main outcome was a composite endpoint of 50% increase in 24h-proteinuria, or eGFR decrease by 50%, or kidney replacement therapy. Results: The median follow-up was 28.3 months. Twenty-three patients met the composite endpoint, 12 for kidney replacement therapy, 6 for an eGFR decrease >50% and 5 for a >50% increase in proteinuria. At time of biopsy, the median proteinuria was 1.9 g/24h and the median eGFR 73.5 mL/min/1.73m2. Among the 102 patients evaluable for C4d, 24 were positive on >30% glomeruli, mainly with a mesangial pattern. In this group, the initial proteinuria was more frequently nephrotic than in the C4d- group (60% vs. 33%, P=0.039). Mesangial hypercellularity was more frequent in the C4d+ group (42% vs. 13%; P=0.006) whereas macroscopic hematuria was more frequent in the C4d- group (18% vs. 0%; P=0.03). After a median follow-up of 28 months, kidney survival did not differ according to C4d status. Conclusion: In a population of adult IgAV patients, glomerular positivity for C4d was associated with the severity of the kidney disease at presentation, but not with subsequent renal function deterioration.